Expression and Clinical Significance of the m6A RNA-Binding Proteins YTHDF2 in Peripheral Blood Mononuclear Cells From New-Onset Ankylosing Spondylitis - Luo, Qing; Guo, Yongqin; Xiao, Qiuyun; Fu, Biqi; Zhang, Lu; Guo, Yang; Huang, Zikun; Li, Junming (Frontiers in Medicine, 2022)
This study has focused on determining the association of m6A methyltransferase [methyltransferase-like 3 (METTL3), methyltransferase-like 14 (METTL14), and Wilms tumor 1-associating protein (WTAP)], demethylase [fat mass and obesity-associated protein (FTO) and alkylation repair homolog protein 5 (ALKBH5)], RNA-binding proteins [YT521-B homology domains 2 (YTHDF2)], and ankylosing spondylitis (AS). A total of 154 specimens, containing 79 patients with new-onset AS and 75 healthy controls (HCs), participated in the study. The mRNA expressions of these m6A methyltransferase, demethylase, and RNA-binding protein in peripheral blood mononuclear cells (PBMCs) were detected by quantitative real-time PCR (qRT-PCR). The data showed that the mRNA expressions of YTHDF2 and ALKBH5 in PBMC from patients with new-onset AS were significantly decreased, and there was a positive correlation between RNA-binding proteins (YTHDF2) and demethylase (ALKBH5) in patients with new-onset AS. Logistic regression analysis demonstrated that the expression of YTHDF2 mRNA in PBMC is a risk factor of AS. Receiver operating characteristic (ROC) analysis of the area under the curve (AUC) for mRNA YTHDF2 in new-onset AS and HC was 0.692, with a cutoff value of <0.8724, a sensitivity of 67%, and a specificity of 63%. Moreover, we constructed a novel predictive model based on a combination of mRNA YTHDF2 and systemic immune-inflammation index (SII) for AS diagnosis (AUC = 0.865, sensitivity = 79.45%, specificity = 84.00%), and the predictive model correlated with the activity and severity of AS. This study indicates that the mRNA expression of YTHDF2 in PBMC may be involved in AS pathogenesis and a predictive model based on a combination of mRNA YTHDF2 and SII acts as a marker for diagnosis and progression of diseases.